Analysis Of The Filter Bubble Algorithm In The Search For Information On The Internet - Bustanur Bustanur; Khairul Hafizi; Nofri Yuhelman (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2022)
This study is a descriptive study of the role of Filter Bable in the realization of religious moderation. This study aims to examine the role that Filterbuble plays in inhibiting human understanding related to the concept of religious moderation advocated by the government through the Ministry of Religious Affairs. This study uses a content approach, that is, an in-depth discussion of the content of written or printed information in various sources that address the issue of religious moderation in the mass media or social media. In the course of this analytical activity, the author conducts activities to examine the tools, techniques, or procedures used to describe or characterize data sets or observations made. These activities include collecting data, grouping data, determining values, analyzing, and drawing conclusions. The effect of a filter bubble in the context of the information society in the age of cyber-religion has the potential to be an obstacle to the realization of religious moderation. This is because a comprehensive understanding of religion is required to realize religious moderation. At the same time, the filter bubble effect can prevent Internet users from the flow of intact information by isolating users in a "bubble" of information personalization.